Efficacy of Percutaneous Posterior Tibial Nerve Stimulation for the Management of Fecal Incontinence in Multiple Sclerosis: A Pilot Study. Issue 7 (25th March 2018) - Sanagapalli, Santosh; Neilan, Laura; Lo, Jack Yu Tung; Anandan, Lavanya; Liwanag, Jorge; Raeburn, Amanda; Athanasakos, Eleni; Zarate‐Lopez, Natalia; Emmanuel, Anton
Abstract : Background: Fecal incontinence is a debilitating and highly prevalent problem among multiple sclerosis patients. Conservative therapies often fail to provide benefit. Posterior tibial nerve stimulation is a minimally invasive neuromodulatory therapy with proven efficacy for fecal incontinence in non‐neurological settings. Objective: To evaluate the efficacy of posterior tibial nerve stimulation in treating multiple sclerosis‐related fecal incontinence. Methods: Consecutive multiple sclerosis patients with fecal incontinence that had failed conservative therapy received posterior tibial nerve stimulation between 2012 and 2015. All patients had previously undergone anorectal physiology tests and endoanal ultrasound. Patients whose Wexner incontinence score reduced below 10 post‐therapy or halved from baseline were deemed responders. Results: Thirty‐three patients (25 female, median age 43 years) were included. Twenty‐three (70%) had urge, 4 (12%) passive, and 9 (27%) mixed fecal incontinence. Twenty‐six (79%) were classified as responders. The majority of subjects had relapsing‐remitting multiple sclerosis (67%); those had a significantly higher response rate (95% vs. 67% and 50% in primary and secondary progressive respectively, P < 0.05). Responders tended to be more symptomatic at baseline and had greater improvements in bowel symptom scores and quality of life scores with therapy. Conclusion: Posterior tibial nerve stimulation demonstrates potential as an effective therapy for fecal incontinence in multiple sclerosis. These findings provide the basis for future more definitive controlled studies.